Obstetric Near Miss Events at a Tertiary Care Centre, Birgunj - Shah, Pravin; Shah, Ravi Kumar; Mushtaq, Rehana; Ansari, Sana; Shrestha, Ruby (Med Phoenix, 2023)
Introduction: Near miss cases are the ones who nearly died but survived a complication that occurred during pregnancy, childbirth, or within 42 days of termination of pregnancy. Near-miss is recognized as the predictor of the level of care and maternal deathand thereforea review of near-miss obstetric eventsis useful to investigate maternal mortality. The study was meant to determine the ratio and nature of near-miss obstetric cases and associated factors. Materials and Methods: This was a prospective observational study done in the Department of Obstetrics and Gynaecology at National Medical College and Teaching Hospital from 1st February 2022 to 31st January 2023. Ethical approval was obtained from IRC (Ref. F-NMC/537/077-078).The near-miss cases were identified among the admitted obstetric cases using the five-factor scoring system and followed till their discharge or death.The assessment of the causes of near-miss cases was done. Results: During the study period, 1163 live births, 33 near-miss cases, and5 maternal mortalities were recorded. The incidence of near-miss was 28.37 per 1000 live births, the mortality index was 13.16% and the near-miss to maternal mortality ratio was 6.6: 1. Haemorrhage (39.39%) was the most common event responsible for near-miss, followed by hypertensive disorders (24.24%). Similarly, cardiovascular (78.79%) was the most common organ dysfunction recorded, followed by hepatic (33.33%). Conclusion: Haemorrhage and hypertensive disorders are the major causes of near-miss events. Identification and evaluation of the factors of near-miss cases can reduce maternal morbidity and mortality, as special preventive actions for the management of its complications can be planned. It is also worth presenting near-miss cases in national indices.